Claudin-binder C-CPE mutants enhance permeability of insulin across human nasal epithelial cells. (12th October 2016) - Kojima, Takashi; Kondoh, Masuo; Keira, Takashi; Takano, Ken-ichi; Kakuki, Takuya; Kaneko, Yakuto; Miyata, Ryo; Nomura, Kazuaki; Obata, Kazufumi; Kohno, Takayuki; Konno, Takumi; Sawada, Norimasa; et al.
Abstract: Objective : Intranasal insulin administration has therapeutic potential for Alzheimer's disease and in intranasal administration across the nasal mucosa, the paracellular pathway regulated by tight junctions is important. The C-terminal fragment of Clostridium perfringens enterotoxin (C-CPE) binds the tight junction protein claudin and disrupts the tight junctional barrier without a cytotoxic effect. The C-CPE mutant called C-CPE 194 binds only to claudin-4, whereas the C-CPE 194 mutant called C-CPE m19 binds not only to claudin-4 but also to claudin-1. Methods : In the present study, to investigate the effects of C-CPE mutants on the tight junctional functions of human nasal epithelial cells (HNECs) and on the permeability of human recombinant insulin across the cells, HNECs were treated with C-CPE 194 and C-CPE m19. Results : C-CPE 194 and C-CPE m19 disrupted the barrier and fence functions without changes in expression of claudin-1, -4, -7, and occludin or cytotoxicity, whereas they transiently increased the activity of ERK1/2 phosphorylation. The disruption of the barrier function caused by C-CPE 194 and C-CPE m19 was prevented by pretreatment with the MAPKK inhibitor U0126. Furthermore, C-CPE 194 and C-CPE m19 significantly enhanced the permeability of human recombinant insulin across HNECs and the permeability was also inhibited by U0126. Conclusion : These findings suggest that C-CPE mutants 194 and m19 can regulate the permeability of insulin across HNECs via the MAPK pathway and may play a crucial role in therapy for the diseases such as Alzheimer's disease via the direct intranasal insulin administration.